Prospective data linkage to facilitate COVID-19 trials – A call to action - Paprica, P Alison; Sydes, Matthew; McGrail, Kimberlyn; Morris, Andrew; Schull, Michael J; Walker, Rhoswyn (International Journal of Population Data Science, 2020)
Many countries around the world are creating COVID-19 trial datasets and databases of COVID-19-related data such as test results that cover entire populations. It is our strong recommendation, and sincere hope, that these data assets will be brought together through record linkage so that their scientific value and impact for society can be amplified. We call on trialists, data stewards and research funders to work together so that prospective linkage of trial data to medical databases becomes the norm, starting with COVID-19 trials.